The causes of teenage maternal mortality at Chris Hani Baragwanath Hospital in Soweto. A review of cases from 1997 to 2011. - Mokone, Nteboheleng Moleboheng Pontsho (My University, 2014)
Introduction The most tragic outcome of a teenage pregnancy is a teenage maternal death. Research from African countries has shown that pregnant teenagers are at increased risk for maternal death when compared with older women, chiefly from complications of hypertension in pregnancy and pregnancy-related sepsis. The objectives of this study were to determine the proportion of maternal deaths accounted for by teenagers, and to describe associated obstetric factors, causes of death and avoidable factors. Setting and methods This was a descriptive retrospective study, using records of all maternal deaths at Chris Hani Baragwanath Hospital (CHBH) from 1997 to 2011. All maternal deaths at CHBH are notified to the national government, and complete patient records have been kept since 1997. All teenage (age less than 20 years) maternal deaths were found by hand-searching all maternal death files for the study period. Demographic and obstetric details were recorded, as well as the primary cause of death and avoidable factors in each case, using the methodology of the Confidential Enquiries into Maternal Deaths in South Africa. Results There were 33 teenage maternal deaths out of a total of 562 deaths (6.1%). Eighteen (54.5%) of the teenagers were 18 or 19 years old. Nine died without having booked for antenatal care.Twenty-six (78.8%) were 28 weeks or more pregnant or postpartum when they died. The most frequent causes of death were hypertensive disorders of pregnancy (n=10; 30.3%), including 9 cases of eclampsia, and non-pregnancy-related infections (n=10; 30.3%), including 6 cases of lower respiratory tract infection and 2 foreign nationals who died of malaria. Among the teenagers who died from non-pregnancy-related infections, 3 were HIV infected, 4 were HIV negative and 3 did not have HIV results. Infrequent causes of death included pregnancy-related sepsis (n=2; 6.1%), and postpartum haemorrhage (n=1; 3.0%). The most frequent avoidable factors were failure to book for antenatal clinic (n=5; 15.2%) and delay in seeking medical help (n=8; 24.2%). Conclusion Maternal deaths in teenagers were infrequent and occurred in a lower proportion of all maternal deaths (6.1%) than expected, based on data suggesting a 13% teenage pregnancy proportion from a study done in 1999 to 2001. This finding differs from those in other African countries. The high frequency of eclampsia is similar to data from other countries, but pregnancy-related sepsis was not frequent. Development and maintenance of adolescent community resources and health services, including improving access to foreign teenagers, may improve health care utilisation by teenagers. Utilisation indicators would include use of contraception, uptake of termination of pregnancy services, and antenatal care attendance for ongoing pregnancies.
Keywords: Mortality; Pregnancy in Adolescence; Causes of Death